EDUCACIÓN, ÉTICA Y POSMODERNIDAD - Boavida, Joâo; Formosinho Sanches, Maria das Dores (Educación XX1, 2012)
Este trabajo pretende llamar la atención y analizar los siguientes problemas contemporáneos. 1. La articulación entre la naturaleza de la educación y el fundamento de la práctica educativa. 2. La necesidad de encontral soluciones eficaces ante la crisis social y el problema cada vez más complejo de sus repercusiones educativas. 3. La necesidad de desarrollar el juicio moral. Palabras clave: Juicio moral, formación humana, educación moral. ABSTRACT The aim ofthis paper is to analyse the following contemporary issues: 1. the articulation between the nature of education and educational practice; 2. the need offinding efficient solutions for social crisis and for the increasingly complex problem of educational effects; 3. and, finally, the need of developping the moral judgment without, forgetting that it is insufficient to solve completely the prohlems raised by the human, moral and social education of contemporary man. key words: moral judgment, human formation, moral formation, nature of education